Global justice in a pluralistic world society - Lafont, Cristina (Estudios de Filosofía, 2008)
In the contemporary discussion on normative models for a new international order, it is widely accepted that international justice requires guaranteeing peace, security and the defense of human rights. However, just as the goals of peace and security are incontrovertible, the same cannot be said for the goal of protecting human rights. The usual candidates for disagreement are the so-called economic and social rights, followed by the political rights to democratic participation. But, unfortunately, not even the right to full equality is unquestioned. Some authors opt for the minimalist strategy of identifying basic human rights, hoping to elicit universal approval within the international community, while others follow a more generous strategy, with the intention of increasing the normative consequences of their proposals. [Fragment]